Pengaruh Brand Ambassador, Brand Image, Dan Customer Experience Terhadap Keputusan Pembelian Produk Scarlett Di Kota Batam - Haifa, Cecilia Putri; Hikmah , Hikmah (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The study is to examine how Scarlett's product purchase decisions in Batam City are influenced by brand ambassadors, brand image, and customer experience. Purposive sampling techniques were used to choose a sample of 204 customers who had used Scarlett goods. Multiple linear regression models, together with data quality, classic assumptions, influence, and hypothesis tests, were used to examine the gathered data. According to the results of linear regression research, brand ambassadors positively influenced purchase decisions by 21.6%, brand image by 20.9%, and customer experience by 47.7%. These three factors taken together may explain 73.9% of the variances in purchasing choices, according to the determination coefficient (R²). T and Test F demonstrate that Scarlett's choice to buy a product in Batam City is positively and significantly influenced by brand ambassadors, brand image, and customer experience, both alone and together. These results offer valuable information for beauty sector product marketing strategies.